In vitro effects of triiodothyronine on the reduced osteogenic potential of bone marrow mesenchymal stem cells of rats with osteoporosis - Boeloni, Jankerle N.; Ocarino, Natália M.; Goes, Alfredo M.; Serakides, Rogéria (Brazilian Journal of Veterinary Pathology, 2015)
Objective: Evaluate the effect of in vitro triiodothyronine (T3) on the reduced osteogenic potential of bone marrow mesenchymal stem cells (BMMSCs) of adult rats with osteoporosis compared with BMMSCs of young and adult rats without osteoporosis. Methods: groups were tested: BMMSCs of young rats; BMMSCs of adult rats without osteoporosis; BMMSCs of adult rats with osteoporosis without T3 and BMMSCs of adult rats with osteoporosis treated with T3 (0.01, 1, 100 and 1000 nM). Alkaline phosphatase activity, MTT reduction, mineralized nodules and gene expression for collagen, osteocalcin, sialoprotein, osteopontin and BMP-2 were evaluated. Results: Osteoporosis increased the alkaline phosphatase activity and reduced the formation of mineralized nodules and expression of collagen and osteopontin in at least one of the observed time points. However, the T3 treatment of BMMSCs of rats with osteoporosis altered these parameters. Conclusion: It was concluded that doses of T3, 0.01 and 1000 nM had a positive effect promoted by increased osteogenic matrix synthesis and collagen expression in at least one of the evaluated time points compared to BMMSCs of rats with osteoporosis without treatment. However, T3 was unable to reach the osteogenic potential of the MSCs of healthy young rats.